Strategi Komunikasi Kepala Sekolah dalam Mengembangkan Kinerja Guru di SD Negeri 13 Talang Kelapa - Rabial Kanada; Saipul Annur; M. Rizki Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This research aims to uncover the communication strategies employed by school principals in enhancing teachers' performance at SD Negeri 13 Talang Kelapa. A qualitative research method was utilized, involving in-depth interviews with selected principals and teachers, along with direct observations within the school environment. The findings indicate that principals utilize various communication strategies, including effective interpersonal communication, relevant media usage, and fostering open and collaborative communication culture. Additionally, principals employ coaching approaches and personal motivation to foster teachers' professional growth. Despite efforts, there remains a need to enhance communication strategies in improving teachers' performance. Supporting factors include effective communication methods, appropriate scheduling, and adequate facilities, while technical disruptions and semantic barriers hinder communication strategies. These findings offer deeper insights into the crucial role of school principals in creating supportive, motivating, and facilitating environments for teachers' professional growth. The conclusion, underscore the importance of effective communication in school management, particularly focusing on the relationship between principals and teachers to enhance the quality of education at SD Negeri 13 Talang Kelapa. Keywords: Communication, Strategy, Performance, School Principal, Teacher